Furanonaphthoquinones from Tabebuia avellanedae induce cell cycle arrest and apoptosis in the human non-small cell lung cancer cell line A549. (March 2015) - Zhang, Li; Tatsuno, Takanori; Hasegawa, Isao; Tadano, Takeshi; Ohta, Tomihisa
Graphical abstract: Highlights: A new furanonaphthoquinone and its analogues were obtained from the inner bark of Tabebuia avellanedae Lorentz ex Griseb. The anticancer effect of the new compound was determined. The effects of the new compound on cell cycle, cell cycle-associated proteins, apoptosis and apoptosis markers were investigated. Abstract: A series of furanonaphthoquinones based on the naphtho[2, 3-b]furan-4, 9-dione skeleton were obtained from water extract of the inner bark of Tabebuia avellanedae Lorentz ex Griseb. The chemical structure of the new compound (3 ) was determined by spectroscopic techniques. Compounds 2 and 3 produced cytotoxicity in A549, SiHa and MCF-7 cells at micromolar concentrations. In addition, results indicated that the position of the phenolic group is of great importance for increasing cytotoxic effect. Furthermore, cell cycle analysis was evaluated by PI staining and apoptosis was determined by annnexin-V FITC/PI staining using flow cytometry analysis. The results showed that compounds 2 and 3 induced the cell cycle arrest and apoptosis at G2/M phase in A549 cells. Investigation of the cyclin protein family members by Western blotting showed that cyclin A and cyclin B protein levels were strongly decreased with the increasing time of incubation with compounds 2 and 3, which may be the major factor that caused G2/M phase arrest. Reverse transcription polymerase chain reaction (RT-PCR) analysis demonstrated that following the exposure of A549 cells to compounds 2 and 3, the level of mRNA expressions of tumor suppressor P53 and apoptotic protein BAX was down-regulated. The caspase-3 enzyme activity was also higher in compounds 2 and 3 exposed A549 cells. Therefore, these furanonaphthoquinones isolated from T. avellanedae are promising leads for potential anticancer drugs.